Corrosion behavior of porous magnesium coated by plasma electrolytic oxidation in simulated body fluid. Issue 9 (2nd April 2019) - Ghasemi, Alireza; Kamrani, Sepideh; Hübler, Daniela; Fleck, Claudia
Abstract: Porous magnesium has a great potential to be used as degradable bone scaffolds. In this study, porous magnesium with 35% percolating porosity has been successfully fabricated through powder metallurgy route utilizing space holders. The intrinsic mechanical properties of the porous magnesium were measured by nanoindentation testing and analyzed with the Oliver–Pharr method. Afterward, a ceramic coating on the surface of the porous magnesium was performed by plasma electrolytic oxidation (PEO) treatment in a silicate‐based solution. The morphology and composition results of the PEO coatings indicated that it is possible to apply a homogenous and adhesive ceramic coating layer on all free surface of the porous magnesium through PEO method. The protective performance of the PEO coatings was evaluated using by potentiodynamic polarization and electrochemical impedance spectroscopy tests in simulated body fluid. The results revealed the PEO coating significantly improves biocorrosion resistance of the porous magnesium. Therefore, it can be used as an effective method to control the degradation rate of porous magnesium implants in the human body. Abstract : The protective performance of plasma electrolytic oxidation (PEO) coatings on the surface of porous magnesium was evaluated by potentiodynamic polarization and electrochemical impedance spectroscopy tests in simulated body fluid. The results revealed the PEO coating significantly improves biocorrosion resistance of the porous magnesium. Therefore, it can be used as an effective method to control the degradation rate of porous magnesium implants in the human body.